Strategi Pemasaran Viral dalam Meningkatkan Awareness Merek di Media Sosial - Melvin Krisdiana Djami Rane; Muammar Revnu Ohara; Andriya Risdwiyanto; Andreas Recki P.; Yeni (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is to determine the effectiveness of viral marketing strategies in increasing brand awareness on social media. This research approach collects data through literature studies, which involve reading literature from various sources including books, journals and reports using qualitative and deductive approaches. The findings in this study are that there are 6 elements of viral marketing that are used to increase effectiveness in increasing brand awareness, namely Providing valuable products or services, Providing easy transfer to others, Increasing, Exploiting common motivations and behaviors, Leveraging existing communication networks, and Leveraging other people's resources. In addition, viral marketing strategies have also proven effective in increasing brand awareness on social media. By utilizing relevant and creative content, the right timing in distributing content, the right audience, high interaction and engagement, and utilizing popular social media platforms such as Instagram, Facebook, TikTok, and YouTube, it can increase brand awareness, expand brand reach and encourage deeper engagement with the audience.